2017
DOI: 10.1016/j.polymertesting.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal cycling and open-hole size on mechanical properties of polymer matrix composites

Abstract: This paper investigates the effects of thermal cycling on mechanical degradation of polymer matrix composites (PMCs). Un-notched and open-hole specimens are tested using developed thermal cycling apparatus and tensile test machine. In addition, the hole-size effect of open-hole tension glass/epoxy composite laminates is investigated. The tensile strength, mass loss and surface degradation of the specimens were obtained during 250 cycles. Experimental results showed that the holes diameter is the main parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…In general, there are no different damage mechanisms between different hole configurations of lontar fiber-reinforced composites. This kind of damage phenomenon was also described by previous study [ 12 ] for quasi-isotropic carbon/epoxy composite.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In general, there are no different damage mechanisms between different hole configurations of lontar fiber-reinforced composites. This kind of damage phenomenon was also described by previous study [ 12 ] for quasi-isotropic carbon/epoxy composite.…”
Section: Resultssupporting
confidence: 81%
“…This work concluded that the increase of hole size produced different damage mechanisms and higher stress concentration at the edge of the hole. In similar terms of the hole size effect on tensile strength of polymer matrix composite, Ghasemi and Moradi [ 12 ] found that composites with smaller holes have higher tensile strength compared to those with bigger holes. The increment of hole size produced larger area of failure and different failure mode.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their low density, nowadays the conventional metallic counterparts are being replaced by FRPs in many LN 2 fuel tanks in storage and transportation. But in‐service conditions, these composites are severely affected by various environmental parameters like humid atmosphere, high temperatures, low and sub‐zero environment, thermal shock, thermal cycling, and also different types of loadings, and often combination of different types of loadings and aforesaid environments . Nowadays, in aerospace related applications the fuel tanks made up of conventional materials are being substituted by advanced polymer matrix composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of experiments available which have been designed based on the Taguchi method and that have analyzed the influence of various parameters such as the lay-up, number of thermal cycles and weight fraction of fibers on the mechanical properties. 810 The mechanical properties of specimens are obtained using the tensile test before and after the thermal cycling load. Also, a regression analysis was developed for modeling the mechanical properties using the effective factors.…”
Section: Problem Formulationmentioning
confidence: 99%